The Roots Cause of the Drug Shortage and Expired Drug Problem at Hospital X - Ni Putu Udayana Antari; I Gede Wayan Sujarna; Ni Wayan Ratih Purnama Sari; Nurul Fatoni; Ni Luh Damayanti; Ni Made Dharma Shantini Suena (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Good drug management in the Hospital Pharmacy Installation is the key to the smooth running of pharmaceutical services. The availability of the necessary drugs at the right time and place affects patient safety and satisfaction. Empty drugs and expired drugs are problems in drug management, mainly Hospital X. Empty drugs result in the replacement of drugs in prescriptions, thus increasing the burden on pharmaceutical services and creating risks for patient safety. Expired drugs cause hospital losses. This study aims to describe the root cause of drug shortages and expired drugs in Hospital X. The research used a qualitative approach to dig deeper into these complex problems—elicitation of data using semi-structured interviews supported by secondary data from the hospital. Data were analyzed using a Fishbone diagram to get a systematic overview of the root causes of problems based on specific domains. The root causes of expired drug problems and empty drug substitution in Hospital X are materials/inputs, methods, people, machinery/equipment, measurement (process evaluation), and the pharmacy facility environment domains.